Eksistensi dan Perubahan dalam Seni Pertunjukan Melayu Riau - Arbi Arbi; Umi Luthfiyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Riau Malay performing arts are an important cultural heritage, serving as a medium for the expression of identity, moral values, and spirituality of the community. Its existence faces challenges due to globalization, social change, and the declining interest of the younger generation. This paper examines the cultural dynamics, changes in function, and preservation strategies of Riau Malay performing arts. The method used is a literature study with analysis of various sources. The results show that digital innovation, government policy, education, cultural festivals, and legal protection are key in maintaining the sustainability of this art. However, preservation is still faced with weak coordination, lack of protection, and the threat of modernization. Therefore, a collaborative and adaptive approach is needed for Riau Malay performing arts to remain sustainable in the modern era.